2020
DOI: 10.1186/s12882-020-01870-1
|View full text |Cite
|
Sign up to set email alerts
|

Caring for older patients with advanced chronic kidney disease and considering their needs: a qualitative study

Abstract: Background: Older patients with advanced chronic kidney disease often do not understand treatment options for renal replacement therapy, conservative kidney management, and advance care planning. It is unclear whether both clinicians and patients have similar perspectives on these treatments and end-of-life care. Thus, the aim of this study was to explore clinician and patient/caregiver perceptions of treatments for end-stage renal disease and advance care planning. Methods: This was a qualitative interview st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(46 reference statements)
0
15
0
2
Order By: Relevance
“…Importantly, newer models of care, such as the Kidney Care Choices program, have emphasized patient activation and the role of kidney clinicians as "principal providers" for older patients with advanced CKD, encouraging greater participation in ACP. [30][31][32][33] Clearer institutional protocols and greater reimbursement for ACP may help. 34 In 2016, the CMS began offering reimbursement to clinicians for ACP discussions, although early data show minimal use by nephrologists.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, newer models of care, such as the Kidney Care Choices program, have emphasized patient activation and the role of kidney clinicians as "principal providers" for older patients with advanced CKD, encouraging greater participation in ACP. [30][31][32][33] Clearer institutional protocols and greater reimbursement for ACP may help. 34 In 2016, the CMS began offering reimbursement to clinicians for ACP discussions, although early data show minimal use by nephrologists.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Prior qualitative research has identified the profound physical and emotional struggles of life with advanced CKD and the numerous barriers to engagement in advance care planning, reinforcing the presence of unmet palliative care needs in this population. [15][16][17][18] However, to the best of our knowledge, there has been no prior work exploring patient and caregiver experiences receiving ambulatory palliative care specific to kidney disease. We previously described patient demographics and clinical activities of an integrated ambulatory nephrology and palliative care clinical program at our institution called The Kidney CARES (Comprehensive Advanced Renal disease and ESRD Support) Program.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted in-depth interviews with clinicians (nephrologists and primary care physicians), older patients and their caregivers at an academic medical centre in Boston, Massachusetts. 35 Specifically, we assessed interviewees’ prior experiences with discussions about kidney replacement therapies and ACP. We found that nephrologists and primary care physicians were mostly aligned with respect to their roles in discussing dialysis and ACP.…”
Section: Methodology and Analysismentioning
confidence: 99%